Exercise capacity and respiratory profile in patients after orthopedic liver transplantation: a follow-up study - Magalhães, Clarissa B. A. (2018)
Introduction: We sought to describe: 1) The influence of orthotopic liver transplantation (OLT) on exercise capacity, pulmonary function and respiratory muscle strength after surgery, 2) The relationship between exercise capacity and symptoms of anxiety a nd depression. Material and methods. Material and methods. Material and methods. Material and methods. Material and methods. This is a prospective follow up study conducted with patients submitted to OLT. All patients were assessed before and 1 month after surgery through measurements: six minute walk test (6MWT), 6 min step test (6MST) and HADS (Hospital Anxiety and Depression Scale). FEV1% (forced expiratory volume), maximal inspiratory pressure (MIP) and maxi- mal expiratory pressure (MEP) were measured in the pre-operative and on 1st, 3rd, 5th day and 1 month after surgery. Results. Results. Results. Results. Results. In 77 patients , 6MWD improved 20.2 m (95%CI 8.1-32.3) and 6MST improved 7.8 steps after surgery (95%CI 3.9-11.6). Change in 6 MWD and 6 MST did not correlated with change HADS. The FEV1% at each time point were 88.8 ± 21.3 before surgery, 32.9 ± 9.9 on 1st day, 39.6 ± 11.5 on 3rd day, 46 ± 12.1 on 5th day and 86.6 ± 21.1 one month after surgery. MIP and MEP values at each time point were -67.4 ± 23.2 and 79.7 ± 26 before surgery, -30.8 ± 12.3 and 36.4 ± 15.4 on 1st day, -38.6 ± 14.1 and 43.8 ± 17 on 3rd day, -45.8 ± 15.9 and 49.7 ± 18.7 on 5th day and -67.1 ± 29.4 and 80.9 ± 23.9 one month after surgery. Conclusion. Conclusion. Conclusion. Conclusion. Conclusion. Ex- ercise capacity was modestly increased after OLT without any correlation with symptoms of anxiety and depression. Pulmonary function and respiratory muscle strength decreased immediately after liver transplantation, and progressively recovered, return ing to baseline values after 1 month.